THE EFFECT OF CIRCULAR ECONOMY AND ENVIRONMENTAL PERFORMANCE ON CORPORATE WASTE DISCLOSURE - Gunady, Devina Caroline; Shanti, Shanti (Jurnal Akuntansi Bisnis, 2025)
Background: Environmental issues caused by the impact of waste are currently a major concern for people around the world. The growing human population every year is the main cause of the increase in waste generation. Waste generation from companies' operational activities has also received attention from the world community, so corporate social environmental responsibility is very important to communicate. The United Nations Sustainable Developmet Goals raised this issue in the 12th SDG's topic of “Responsible Consumption and Production”.Objective: This study aims to examine the effect of circular economy and environmental performance on corpotate waste disclosure, with financial performance, company size, and company value as control variables.Research Methods: This research is a quantitative study that focuses on manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the 2021-2023 period. The method used in this research is multiple linear regression analysis.Research Results: The results showed that the circular economy and environmental performance has a positive and significant effect on corporate waste disclosure. This study concludes that companies that are committed to circular economy practices and have good environmental performance tend to make more transparent waste disclosures. The results of this study also found that the control variables of financial performance and firm value do not have a significant effect, while the control variable of firm size has a significant effect.Originality/Novelty of Research: This study provides new insight by using Social Return On Investment (SROI) as a measurement of environmental performance and incorporating the effect of circular economy on corporate waste disclosure.